(untitled) (Academicia Globe: Inderscience Research, 2024)
Digitalization has emerged as a transformative force, reshaping economies worldwide by driving innovation, enhancing productivity, and fostering new business models. This article explores the impact of digitalization on economic growth, with a particular focus on emerging markets. The study examines how digital technologies contribute to economic development by enabling access to global markets, improving efficiency, and stimulating entrepreneurial activities. However, it also highlights the challenges faced by emerging markets, including digital infrastructure gaps, cybersecurity risks, and the digital divide. The findings suggest that while digitalization presents significant opportunities for economic growth, these benefits can only be fully realized through strategic investments in digital infrastructure, education, and regulatory frameworks. By addressing these challenges, emerging markets can harness the full potential of digitalization to achieve sustainable economic growth and development.